A spoon full of studies helps the comparison go down: a comparative analysis of Tulving’s spoon test - Scarf, Damian; Smith, Christopher; Stuart, Michael (Frontiers in Psychology, 2014)
Mental time travel refers to the ability to cast one’s mind back in time to re-experience a past event and forward in time to pre-experience events that may occur in the future. Endel Tulving (2005), an authority on mental time travel, holds that this ability is unique to humans. Anticipating that comparative psychologists would challenge this claim, Tulving (2005) proposed his spoon test, a test specifically designed to assess whether nonhuman animals are capable of mental time travel. A number of studies have now employed the spoon test to assess mental time travel in nonhuman animals. Here, we review the evidence for mental time travel in primates. To provide a benchmark, we also review studies that have employed the spoon test with preschool children. The review demonstrates that if we compare the performance of great apes to that of preschool children, and hold them to the same criteria, the data suggest mental travel is present but not ubiquitous in great apes.